PREVALENCE OF MULTI DRUG RESISTANCE (MDR) AMONG DIVERSE BACTERIAL COMMUNITIES IN BHAVANI RIVER: AN UNADDRESSED THREAT - Sen, Shampa (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Improper management of river water due to industrial effluents and domestic discharges raised serious issues in the availability and quality of water. Environmental standards remains unconsidered by most of the Industries located upstream of the rivers. Our work focused on accessing the quality and bacterial diversity of rapidly polluted BhavaniRiver, the mainline water resource of the Kongunadu region. Water samples were collected from two sites used by the people for routine use. At the sites of analysis, the water displayed physicochemical values far away from the permissible limits of World Health Organization (WHO). Phylogenetic diversity prediction by 16s ribosomal DNA (rDNA) gene sequencing method disclosed the presence of two major phyla, Firmicutes (71%) and Proteobacteria (21%) affiliated to different genera (Bacillus, Paenibacillus, Lysinibacillus, Staphylococcus, Pseudomonas and Acinetobacter). Of the total population, 35% of the isolates represent novel phenotypes. Antibiotic susceptibility test indicated that >60% of the total bacterial strains showed strong resistance to all the antibiotics. The cumulative resistance percentage ranged from 64-82 signifying their adaptive nature to Multi Drug Resistance (MDR). Key words: Multi Drug Resistance, physiochemical analysis, phylogenetic diversityÂ 